The Role of Self Concept in Forming Students’ Self Confidence in Public Speaking - Ngefak, Amin R; Ndun, Lesly N.; Olbata, Yabes (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
Public speaking with confidence is one of the most important skills in education, especially for university students. In fact, many students still lack confidence in public speaking, while others are very good at it. Self-concept is an important factor that influences students' self-confidence in public speaking. This study aimed to explore the role of self-concept in building students' confidence in public speaking. It used a qualitative descriptive method and interview as research instrument. Students in the public speaking class of the English Education program at Institut Pendidikan Soe were involved in the study. The results showed that self-concept has three important roles in building students' confidence, namely: as a foundation of confidence, overcome anxiety and doubt, and key to facing challenges. This also confirms that a positive self-concept helps students have high self-confidence.